Perancangan Sistem Pendukung Keputusan Pemilihan Guru Terbaik Dengan Pendekatan User Centered Design - Muhammad Rafie Chautie; M Rudi Sanjaya; Endang Lestari; Bayu Wijaya Putra (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
Teacher evaluation is a common practice in the world of education. It is useful to determine the quality of teaching performed by teachers. Assessment and evaluation also aim to stimulate the performance of teachers in the learning process. Evaluation and assessment of teachers at Pesantren Miftahul Jannah have not been maximally implemented, subjective assessments from decision-makers often arise, making it difficult to determine the best teachers. User-centered design method is used to create solutions based on user needs. In this study, the design of a decision support system for selecting the best teachers is discussed by applying the user-centered design method to assist in assessing the best teachers. With this method, it is expected that the solutions provided can help solve the problem. The results of this study provide a design and prototype. The prototype that has been built has been tested using the System Usability Scale (SUS) method with a score of 71.6 and received an adjective rating of B or good.